Factors affecting mothers who have babies in breastfeeding at Tuan Rondahaim General Hospital, Simalungun Regency - Henry Kurniawan; Sekar Pembayun (Institute of Computer Science (IOCS), 2022)
The impact if the baby is not given breast milk can reduce the baby's weight, the baby will also get sick easily because he does not get immunoglobulin substances. For this reason, researchers want to know the factors that influence mothers who have babies in breastfeeding at RSU Tuan Rondahaim Simalungun Regency in 2016. This research was conducted at RSU Tuan Rondahaim Simalungun Regency in 2016 with a population of 30 people and taking samples using the total sampling technique where all population used as sampling. The results of the study were that the majority were aged 19-24 years, namely 13 people (43.3%), the majority had high school education, namely 13 people (43.3%), the majority had jobs as entrepreneurs, namely 10 people (33.3%), the majority had lack of knowledge, namely 20 people (66.7%), the majority had a disapproving attitude, namely 21 people (70%), the majority received support from husbands/family, namely 22 people (73.3%), the majority received support from health workers, namely 21 people (70%). Mothers really need to find as much information as possible about exclusive breastfeeding.